'Indigenous Peoples' and land: Comparing communal land titling and its implications in Cambodia and Laos. (December 2013) - Baird, Ian G.
Abstract In 2001 a new Land Law was adopted in Cambodia. It was significant because – for the first time – it recognised a new legal category of people, 'Indigenous Peoples' or chuncheat daoem pheak tech in Khmer, and it also introduced the legal concept of communal land rights to Cambodia. Indigenous Peoples are not mentioned in the 1993 constitution of Cambodia or any legislation pre‐dating the 2001 Land Law. However, Cambodia's 2002 Forestry Law also followed the trend by recognising 'Indigenous Peoples'. These laws have been both symbolically and practically important, as they have provided government‐mandated legitimacy to Indigenous identities and associated land and forest rights, including communal land rights, and have been ontologically significant in dividing Indigenous and non‐Indigenous Peoples on legal grounds. Over a decade after the 2001 Land Law was promulgated, this article considers some aspects of its effects. In particular, when compared with the potential for developing communal land rights in Laos, one has to wonder how advantageous it is to adopt Indigenous identities and the types of communal land rights and community forestry rights presently possible in Cambodia.